Integration of SDG values in Indonesian language course learning - Tekad Budiantoro (Privietlab, 2026)
The Sustainable Development Goals (SDGs) have emerged as a global agenda to address challenges such as social inequality, environmental degradation, and the quality of education. Higher education plays a strategic role in achieving these goals by fostering students’ critical thinking, academic literacy, and social responsibility. This study employs a Systematic Literature Review (SLR) of scholarly publications from 2025 to examine the integration of SDG values into Indonesian Language courses in higher education. The review identifies key themes, including the role of higher education in SDG implementation, academic literacy development, character formation, social awareness, and strategies for integrating the SDGs into language learning. The findings indicate that Indonesian Language courses possess significant potential as a medium for SDG integration because of their emphasis on academic literacy, critical thinking, and scientific communication. However, the review also reveals that SDG integration remains partial and unsystematic, highlighting the need for a structured conceptual framework. This study recommends the planned incorporation of SDG values into learning objectives, instructional materials, teaching strategies, and assessments, as well as the development of SDG-based learning guides for lecturers. The results provide theoretical and practical implications for enhancing Indonesian Language instruction in alignment with sustainable development.